Patient handovers within the hospital: translating knowledge from motor racing to healthcare. - Catchpole, K; Sellers, R; Goldman, A; McCulloch, P; Hignett, S (2010)
INTRODUCTION: This paper expands the analogy between motor racing team pit stops and patient handovers. Previous studies demonstrated how the handover of patients following surgery could be improved by learning from a motor racing team. This has been extended to include contributions from several motor racing teams, and by examining transfers at several different interfaces at a non-specialist UK teaching hospital. METHODS: Letters of invitation were sent to the technical managers of nine Formula 1 motor racing teams. Semistructured interviews were carried out at a UK teaching hospital with 10 clinical staff involved in the handover of patients from surgery to recovery and intensive care. RESULTS: Three themes emerged from the motor racing responses; (1) proactive learning with briefings and checklists to prevent errors; (2) active management using technology to transfer information, and (3) post hoc learning from the storage and analysis of electronic data records. The eight healthcare themes were: historical working practice; problems during transfer; poor awareness of handover protocols; poor team coordination; time pressure; lack of consistency in handover practice; poor communication of important information; and awareness that handover was a potential threat to patient safety. CONCLUSIONS: The lessons from motor racing can be applied to healthcare for proactive planning, active management and post hoc learning. Other high-risk industries see standardisation of working practices, interpersonal communication, consistency and continuous development as fundamental for success. The application of these concepts would result in improvements in the quality and safety of the patient handover process.